2017
DOI: 10.1097/md.0000000000006392
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of aromatic hydrocarbon receptor and its repressor gene polymorphisms with risk of rheumatoid arthritis in Han Chinese populations

Abstract: The goal of this study was to evaluate the potential relationship among polymorphisms of aromatic hydrocarbon receptor, aromatic hydrocarbon receptor repressor, and rheumatoid arthritis (RA) susceptibility as well as the association among the polymorphisms of aromatic hydrocarbon receptor, aromatic hydrocarbon receptor repressor, and their expression.We performed a hospital-based, case–control study of 400 patients with RA and 726 healthy controls in Han Chinese populations. Two single-nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However, our study did not indicate a significant association of AHR rs2066853, rs2282885 polymorphism with RA susceptibility, and rs2158041 was excluded as it did not satisfy HWE. Consistent with our findings, Cheng et al demonstrated that rs2066853 polymorphism did not have any effect on RA susceptibility in Han Chinese populations ( 31 ). These results suggested that AHR gene variation might not be associated with RA, however, other functional SNPs required further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…However, our study did not indicate a significant association of AHR rs2066853, rs2282885 polymorphism with RA susceptibility, and rs2158041 was excluded as it did not satisfy HWE. Consistent with our findings, Cheng et al demonstrated that rs2066853 polymorphism did not have any effect on RA susceptibility in Han Chinese populations ( 31 ). These results suggested that AHR gene variation might not be associated with RA, however, other functional SNPs required further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Structural work shows that AhRR acts by competitively repressing AhR binding to ARNT and target DNA (37). Furthermore, AhRR levels have been shown to decline in a variety of disease states ranging from rheumatoid arthritis (38) to lung cancer (39). Interestingly, DNA methylation at AhRR has also been shown to be a marker for smoking and was correlated with future smoking morbidity and mortality (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cheng et al evaluated the potential relationship among polymorphisms of AhR and aromatic hydrocarbon receptor repressor ( AhRR ), and RA susceptibility in Han Chinese populations. It has been observed that only rs2292596 in AHRR is significantly associated with RA risk [ 21 ]. Moreover, in the literature, there is no data about this polymorphism and MTX response.…”
Section: Discussionmentioning
confidence: 99%
“…So far c.1933G > C (rs34453673) has only been mentioned in the study on CYP1A2 activity, where the association of this SNP was not proved [ 20 ]. In the case of c.565C > G (rs2292596), the association of this variant with RA risk in the Chinese Han population has been analyzed [ 21 ] and in few other studies associated with infertility [ 22 , 23 ] or xenobiotic metabolism [ 20 , 24 ].…”
Section: Introductionmentioning
confidence: 99%